Beam Shaping Assembly Optimization for Boron Neutron Capture Therapy Facility Based on Cyclotron 30 MeV as Neutron Source - Fauzi, Arief; Tsurayya, Afifah Hana; Harish, Ahmad Faisal; Wijaya, Gede Sutresna (Universitas Gadjah Mada, 2018)
A design of beam shaping assembly (BSA) installed on cyclotron 30 MeV model neutron source for boron neutron capture therapy (BNCT) has been optimized using simulator software of Monte Carlo N-Particle Extended (MCNPX). The Beryllium target with thickness of 0.55 cm is simulated to be bombarded with 30 MeV of proton beam. In this design, the parameter regarding beam characteristics for BNCT treatment has been improved, which is ratio of fast neutron dose and epithermal neutron flux. TiF3 is replaced to 30 cm of 27Al as moderator, and 1.5 cm of 32S is combined with 28 cm of 60Ni as neutron filter. Eventually, this design produces epithermal neutron flux of 2.33 × 109, ratio between fast neutron dose and epithermal neutron flux of 2.12 × 10-13,ratio between gamma dose and epithermal neutron flux of 1.00 × 10-13, ratio between thermal neutron flux and epithermal neutron flux is 0.047, and ration between particle current and total neutron flux is 0.56.